Pelota ; Motion Picture - Leth, Jorgen; Holmberg, Dan; John, Ole (Danish Film Institute, 2007)
Pelota (1983): Pelota is a Basque game played with the hands. For generations, Basque men have played this unique sport of hitting a hard leather ball against a wall. Large "frontons" are set up for the game which attracts great public interest, in both the game itself and the ritualised betting that goes on as it is played. Through the film, Leth gives us an insight into a fascinating sport and not least those who play it - the stars and the legends - but also the many players in streets and alleyways. The film places pelota in its cultural context and imparts feelings and stories about the Basques' unique national character. [Beiheft]
Keywords: DVD-Video